Neurofeedback for the enhancement of athletic performance and physical balance - Hammond, D. C. (The Journal of the American Board of Sport Psychology, 2007)
Neurofeedback (EEG biofeedback) holds potential for retraining brainwave activity to enhance optimal performance in athletes in various sports. Neurofeedback has been shown to have potential for quieting the mind to improve performance in archery, for example. It can also be used to improve concentration and focus, to improve cognitive function and emotional control following concussions and mild head injuries, and it has untapped potential to increase physical balance in gymnastics, ice skating, skiing, and other areas of performance. Clinical examples are provided on the use of neurofeedback to improve physical balance and controlled research is called for.